EFFORTS TO INCREASE PUBLIC PARTICIPATION IN THE FACE OF DEMOCRATIC ELECTIONS IN INDONESIA - Sutowo (Media Inovasi Pendidikan dan Publikasi, 2023)
The purpose of writing this article is to find out the role of political parties in organizing general elections. The writing method used in this study is a qualitative descriptive writing method which describes this research in the form of descriptive sentences based on facts and data. From these arguments, we can conclude that democracy has unique advantages because it reflects the aspirations of the people in every decision-making. Society as the main actor in a democratic country plays a very important role. One of the functions of society in a democratic country is public participation in politics, in this case general elections. Local governments have a very important role in determining executive and legislative power both at the center and in the regions. Therefore, civic education is needed which the public must know so that they don't just vote or participate in realizing a democratic party. Good civics education produces wise people not to choose the wrong leaders and representatives. Thus, the wishes and expectations of the people can be communicated and implemented by the government.